Influência do Compartilhamento de Informações, da Favorabilidade Orçamentária e do Compromisso com as Metas Orçamentárias na Relação entre Participação Orçamentária e o Desempenho Gerencial - Faria, Hugo Micael de Oliveira (2024)
Understanding budgetary processes and their effects on human behavior at work represents an important aspect of study in the managerial area of accounting. Among its approaches, the analysis of its effects on managerial performance in the budgetary context is a topic that requires further investigation, given the conflicting results identified in the literature. The use of controls that enable better decision-making and the qualification of management processes provides new understandings to the organizational environment. In this sense, the budget is one of these control instruments used for this purpose. In controllership, the use of the budget helps controllers manage their work assignments. Although, in some cases, the controller may be one of the actors responsible for preparing the budget, he or she also reports to his or her superiors regarding his or her area of responsibility. For this reason, understanding the factors influencing managerial performance in the budgetary context becomes an important research gap to be explored in the field of management accounting studies. In this context, this research evaluates the influence of vertical information sharing (superior vs. subordinate), budget favorability and commitment to budget goals on the relationship between budget participation and the managerial performance of controllers of industrial companies operating in Brazil. Descriptive research, with a quantitative approach (and use of structural equation modeling), was carried out through a survey, with the application of a questionnaire through the LinkedIn® business network. The sample analyzed was made up of 257 managers in the controlling area and with budgetary responsibility in these organizations. The results found showed that budget participation had a positive and direct influence on information sharing and budget favorability, but the same does not occur in terms of commitment to budget goals and managerial performance, which shows that such relationships may not occur directly, but influenced by other intervening variables. The effects of budget participation on commitment to budget goals occur when information is shared. The interaction between these variables (information sharing and commitment to budgetary targets) enhances the controllers' managerial performance, influencing it positively. The results also revealed that budget favorability does not have a significant influence on commitment to budget goals and managerial performance. This evidence shows that budgetary participation may not be sufficient when put alone to reflect high levels of managerial performance, suggesting the need for sharing and availability of information, and for controllers' commitment to the established budgetary goals, so that they can achieve better performance. high management. These findings contribute to management research in the accounting area, revealing the interactions that exist between the variables investigated in this research, and their intervening effects on the relationship between budgetary participation and managerial performance.